Analisis Kepuasan dan Kesetiaan Pelanggan Berbelanja Pada E-Commerce Shopee - Himyar Pasrizal; Nurul Hidayah; Nurul Nazifah; Rahmi Nabila; Nurul Aisyah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study aims to analyze the influence of service quality, application usability, and purchasing experience on customer satisfaction and their impact on customer loyalty on the Shopee platform. This study uses a quantitative approach with a survey procedure. Data collection techniques were carried out through questionnaires designed to measure variables relevant to the planned analysis. Data analysis techniques used were descriptive and quantitative statistical analysis, including a comparison between customer perceptions of the service received and their expectations to measure customer satisfaction and loyalty. The results show that consumer trust in a product is positively correlated with their level of loyalty. The level of alignment with customer satisfaction reached an average of 90.13%, indicating that satisfied customers tend to be loyal and plan to reuse the Shopee platform. These findings imply that Shopee needs to continue to innovate and improve its offerings to retain customers amidst increasingly fierce competition in the e-commerce sector